Intraoperative pressure injury and risk factors in long-term surgical interventions: Uzun süreli cerrahi girişimlerde ameliyat sırası basınç yaralanması ve risk faktörleri - İpek, Büşra and Sayın, Yazile (Journal of Human Sciences, 2022)
Background: If the operation time is 60 minutes or longer, the patient’s risk of pressure injury increases. Aim: This study aims to determine the prevalence and risk factors for intraoperatively acquired pressure injury (IAPI) in patients who underwent surgery for 60 ≥ minutes in a hospital in Turkey. Methods: The research is a cross-sectional, descriptive, prospective design. Data were collected in the perioperative period (N=200). Sociodemographic and Clinical Characteristics Form and 3S intraoperative pressure injury risk assessment scale were used for data collection. Findings: IAPI occurred in 18.0% of participants. In this study, there was a statistically significant correlation with women ([RR: relative risk]:1.242, 95%, CI [confidence interval]: 0.484-3.190) at risk of pressure injury, those with chronic diseases and those who had major surgery (RR: 11.569, 95%, CI: 2.029-65.954). In addition, the patient’s position during surgery posed a 2.6 times (95% CI: 0.552-12.674) risk for pressure injury. Based on IRAS score, there was a significant relationship between the time of the operation (RR:2.051, 95% CI: 1.113-3.780), and the intraoperative stress (RR:4.338, 95% CI: 1.815-10.369) for the risk of pressure injury. Conclusion: IAPI remains a significant problem in the operating room. In this study, according to sociodemographic characteristics, being female, having a history of chronic disease and being a candidate for major surgery may cause the intraoperative pressure injury. According to 3S- IRAS, long operative time and high skin stress score may create a significant risk of intraoperative pressure injury. Perioperative nurses should assess the risk of each surgical patient and provide position support for the patient during the surgical procedure. Keywords: Surgery; pressure injury; intraoperative; risk factors; prevalence